Sustainability of Maintaining Glass Collections - David Thickett; Antanas Mėlinis (Heritage)
Maintaining a tight RH range for unstable glass is energy- and carbon-intensive. The carbon footprint of several methods for controlling showcases and storerooms, including sorbents, dehumidifiers and sorbents, Miniclima, and RK2, has been measured. Dehumidifiers outperformed Miniclima and RK2 units in control capability, but all three exhibited a higher carbon footprint than passive control methods. However, tailoring the right conditions for the right objects is crucial. The decay of different glass compositions in atmospheric conditions was measured using surface ion swabbing. Conditions below 40% in addition to forced air movement universally slowed deterioration. Formic acid was found to significantly accelerate glass alteration but could be removed using the RK2 unit.